Ecological ICMS: the experience of some brazilian states and possibilities for the State of Bahia (Research, Society and Development, 2020)
The study aimed to examine a viable alternative to the issue of environmental problems, which is the insertion of environmental taxation, through the ICMS Ecológico, an instrument of public policy that enables States to promote the preservation of the environment. It refers to an exploratory work and is based on a quantitative approach, developed with a focus on the State of Bahia, which will verify the distribution of the Ecological ICMS and possible repercussions of the implementation in the State of Bahia, presenting an estimate of the possible collection and also the results already achieved by other States, such as Paraná, Pernambuco, Ceará, São Paulo, Rio Grande do Sul, among others. The ICMS-E has already shown good responses in the eighteen Brazilian states, opening up a range of possibilities for the other federated entities to increase development in favor of protecting biodiversity in their territories. Thus, it is concluded that the degradation of the environment is a global concern, requiring the realization of public policies that enable trajectories for the protection of nature.